2006
DOI: 10.1103/physrevd.74.023001
|View full text |Cite
|
Sign up to set email alerts
|

Capture rates of compact objects by supermassive black holes

Abstract: Capture rates of compact objects were calculated by using a recent solution of the Fokker-Planck equation in energy-space, including two-body resonant effects. The fraction of compact objects (white dwarfs, neutron stars and stellar black holes) was estimated as a function of the luminosity of the galaxy from a new grid of evolutionary models. Stellar mass densities at the influence radius of central supermassive black holes were derived from brightness profiles obtained by Hubble Space Telescope observations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…These models indicate that, in the present-day universe, MBHs might be absent or under-grown in a significant fraction of galaxies with a velocity dispersion below 100 km s −1 [315]. For these reasons, it might be wise not to assume the existence of a large population of MBHs with M • 2 × 10 6 M for conservative estimates of EMRI detection rates [76]. This uncertainty will probably be decreased by the time LISA flies as present and future observations in the electro-magnetic domain will help constrain the low-mass end of the MBH population in nearby galaxies, as well as the characteristics of the nuclei in which they reside.…”
Section: Astrophysical Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These models indicate that, in the present-day universe, MBHs might be absent or under-grown in a significant fraction of galaxies with a velocity dispersion below 100 km s −1 [315]. For these reasons, it might be wise not to assume the existence of a large population of MBHs with M • 2 × 10 6 M for conservative estimates of EMRI detection rates [76]. This uncertainty will probably be decreased by the time LISA flies as present and future observations in the electro-magnetic domain will help constrain the low-mass end of the MBH population in nearby galaxies, as well as the characteristics of the nuclei in which they reside.…”
Section: Astrophysical Uncertaintiesmentioning
confidence: 99%
“…Nevertheless, although they should be envisaged as powerful tools to make an initial, fast exploration of the parameter space, the results give us tendencies of the system, rather than an accurate answer [9]. Studying the Astrophysical I/EMRI problem requires a meticulous characterization of the orbital parameters, so that approximate techniques should be regarded as exploratory only [76].…”
Section: Stellar Dynamics For Galactic Nucleimentioning
confidence: 99%
“…These kicks can be large enough to eject the black hole from its host galaxy. If these black-hole merger kicks are significant for black holes merging in the centers of galaxies, the number of black holes with M < 2 × 10 6 M may therefore be significantly depleted [147].…”
Section: Extreme-mass-ratio Inspiralsmentioning
confidence: 99%
“…A primary source of interest in WD-MBH interactions has been their potential as sources of both electromagnetic and gravitational wave emission (Ivanov & Papaloizou 2007;Rosswog et al 2008aRosswog et al , 2008bRosswog et al , 2009Sesana et al 2008;Zalamea et al 2010;Haas et al 2012;Dai & Blandford 2013;Cheng & Evans 2013), especially as these events, if observed, would constrain the MBH mass function at low masses (e.g., de Freitas Pacheco et al 2006). Chirp waveforms have been computed for single, disruptive passages (e.g., Rosswog et al 2009;Haas et al 2012) and should be detectible only if the source is within ∼1 Mpc given a 10 5 M MBH ).…”
Section: Prospects For Simultaneous Electromagnetic and Gravitationalmentioning
confidence: 99%